 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
If tan β = n sin α cos α/1-n sin^2 α , prove that tan (α - β) = (1- n) tan α

```
2 years ago

```							thanks 4 askin ananya.tan (α - β) = [tanα - tanβ]/[1+tanαtanβ]....(1)but   tan β = n sin α cos α/1-n sin^2α.......(2) ,we see that sin α cos α=sin2α/2=tanα/[1+tan^2α] and sin^2α= tan^2α/[1+tan^2α] . now substitute these values in (2) and simplify, we gettanβ= ntanα/[1+tan^2α – ntan^2α]substitute this value in (1), and simplify, we have tan (α - β) = tan (α)[1+tan^2α – ntan^2α – n]/[1+tan^2α]factoring [1+tan^2α – ntan^2α – n] as (1-n)(1+tan^2α) we have=tanα (1-n)(1+tan^2α)/(1+tan^2α)= (1- n) tan αhence proved
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Trigonometry

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 31 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions